2010
DOI: 10.1111/j.1754-4505.2010.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Treating patients with Autism Spectrum Disorder—SCDA members’ attitudes and behavior

Abstract: The goal of this study was to explore (a) the attitudes and behavior of members of the Special Care Dentistry Association (SCDA) who self-identified as treating patients with Autism Spectrum Disorders (ASD) and (b) the relationship between their professional attitudes and behaviors concerning these patients. Data were collected from 75 SCDA members who responded to an anonymous web-based survey on the SCDA website. The majority of respondents liked to treat children and adults with ASD (57%/56.9%). They treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 31 publications
0
36
0
1
Order By: Relevance
“…Accommodations such as using picture schedules or boards, social stories to prepare children for dental visits, visual aids, speaking in short, concise phrases that are repeated often, behavioral training and modeling, and/or desensitization appointments may be helpful with this population. Some of these techniques have already been utilized for children with ASD during dental care and in other arenas with success [5, 14, 4346]. Additionally, adapting the dental environment to decrease arousal may be beneficial for the ASD population, as physiological and behavioral distress were found to be moderately to strongly correlated in this study.…”
Section: Discussionmentioning
confidence: 66%
“…Accommodations such as using picture schedules or boards, social stories to prepare children for dental visits, visual aids, speaking in short, concise phrases that are repeated often, behavioral training and modeling, and/or desensitization appointments may be helpful with this population. Some of these techniques have already been utilized for children with ASD during dental care and in other arenas with success [5, 14, 4346]. Additionally, adapting the dental environment to decrease arousal may be beneficial for the ASD population, as physiological and behavioral distress were found to be moderately to strongly correlated in this study.…”
Section: Discussionmentioning
confidence: 66%
“…Flexibility and creativity are essential in the dental office, as simultaneous use of multiple accommodations may benefit children with special needs, especially those with ASD (Weil et al, 2011). In fact, one study surveying Special Care Dentistry Association members found that respondents utilized an average of 6.34 accommodations to address difficulties with communication, routine, and social interactions when providing dental care for children with ASD (Weil et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Flexibility and creativity are essential in the dental office, as simultaneous use of multiple accommodations may benefit children with special needs, especially those with ASD (Weil et al, 2011). In fact, one study surveying Special Care Dentistry Association members found that respondents utilized an average of 6.34 accommodations to address difficulties with communication, routine, and social interactions when providing dental care for children with ASD (Weil et al, 2011). As mentioned earlier, a recent study adapted the visual, auditory, and tactile environment of the dental operatory during routine dental cleanings, successfully decreasing the physiological distress, behavioral distress, perception of pain, and sensory discomfort in children with ASD (Cermak et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that approximately 30–50% of children with ASD are capable of receiving dental care using only behavioral techniques . Table lists a number of factors have been associated with greater difficulty accepting dental care …”
Section: An Example Clinical Protocol To Improve Patient Visitsmentioning
confidence: 99%